Collective resonances in hybrid photonic-plasmonic nanostructures. (March 2020) - Ershov, Alexander E.; Bikbaev, Rashid G.; Rasskazov, Ilia L.; Gerasimov, Valeriy S.; Timofeev, Ivan V.; Polyutov, Sergey P.; Karpov, Sergey V.
Abstract: We present the theoretical model to predict the spectral position of Rayleigh anomalies emerged in hybrid system consisting of periodic array of plasmonic nanodisks embeded into the middle of defect layer of 1D photonic crystal (PhC). The spectral positions of these new emerged Rayleigh anomalies agree well with the results of exact simulations with Finite-Difference Time-Domain (FDTD) method.